2022
DOI: 10.1142/s0217984922300034
|View full text |Cite
|
Sign up to set email alerts
|

Electron acceleration by relativistic pondermotive force in the interaction of intense laser pulse with an axially inhomogeneous underdense plasma

Abstract: In this paper, electron acceleration by relativistic pondermotive force has been studied in the interaction of intense laser pulse with an axially inhomogeneous underdense plasma. The results show that the relativistic ponderomotive nonlinearity causes obvious beam self-focusing and a highly energetic electron can be achieved in the plasma, moreover, the high-energy electron would be automatically ejected by the ponderomotive force without adding any additional extractor. In addition, it is found that the real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…They have also studied the excitation of UHW and electron acceleration by a Laguerre-Gaussian laser beam in the magnetoplasma in the presence of relativistic and ponderomotive nonlinearities [25]. Other relevant studies on electron acceleration by intense laser beams in plasma have been reported in the literature [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…They have also studied the excitation of UHW and electron acceleration by a Laguerre-Gaussian laser beam in the magnetoplasma in the presence of relativistic and ponderomotive nonlinearities [25]. Other relevant studies on electron acceleration by intense laser beams in plasma have been reported in the literature [26][27][28].…”
Section: Introductionmentioning
confidence: 99%